2021
DOI: 10.3201/eid2702.201960
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 in Guilan Province, Iran, April 2020

Abstract: We determined the seroprevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in an affected area in northern Iran in April 2020. Antibodies to SARS-CoV-2 were detected in 528 persons by using rapid tests. Adjusted prevalence of SARS-CoV-2 seropositivity was 22.2% (95% CI 16.4%-28.5%).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 9 publications
5
62
3
Order By: Relevance
“…In the USA the prevalence of seropositivity was 19.1% in New York City in the month of April (30), and at the same time it was 4.65% in California (31). High seropositivity rates (respectively 22%, 42% and 66%) have been reported in April 2020 in Guilan, Iran and in July 2020 both in Bergamo, Italy and in Manaus, Brazil (32, 33, 34).…”
Section: Discussionmentioning
confidence: 99%
“…In the USA the prevalence of seropositivity was 19.1% in New York City in the month of April (30), and at the same time it was 4.65% in California (31). High seropositivity rates (respectively 22%, 42% and 66%) have been reported in April 2020 in Guilan, Iran and in July 2020 both in Bergamo, Italy and in Manaus, Brazil (32, 33, 34).…”
Section: Discussionmentioning
confidence: 99%
“…This study was performed on a subset of participants from a seroprevalence survey in the north of Iran. The details of the study were described elsewhere [15]. Briefly, a random sample of general population permanently residing in Guilan province, irrespective of age, was selected through stratified multistage (cluster) sampling and during [11][12][13][14][15][16][17][18][19] April 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the study were described elsewhere [15]. Briefly, a random sample of general population permanently residing in Guilan province, irrespective of age, was selected through stratified multistage (cluster) sampling and during [11][12][13][14][15][16][17][18][19] April 2020. Residents of institutional living centres such as nursing homes, prisons and boarding schools, and those people who did not want to participate, were under active treatment of COVID-19, or had any contraindication to venepuncture were not invited to the study.…”
Section: Methodsmentioning
confidence: 99%
“…A study in Mumbai from February 2021 showed that seroprevalence in non-slums was 16.1%, while it was as high as 54.1% in slums (32). Furthermore, recent individual studies from late 2020 and early 2021 have shown seroprevalence ranging from 0.09% to 22.2% (33)(34)(35)(36)(37)(38). Some of these studies have used a Bayesian approach for accounting for misclassification bias, which represents more properly the data obtained in these seroprevalence studies (35,36).…”
Section: Seroprevalencementioning
confidence: 99%